3F.007 Bisensory occupational overload as a result of expressive dysphasia syndrome. (14th March 2021) - Hanson, Dale
Abstract : Background: We describe a newly identified manifestation of expressive dysphasia (impaired language production resulting in an inability to meaningfully communicate). Bi-sensory Occupational Overload as a Result of Expressive Dysphasia. This occupational disease is transmitted orally and is highly contagious in large social gatherings. Methods: Action research into the effects, transmission and severity of Bi-sensory Occupational Overload as a Result of Expressive Dysphasia was conducted biennially over a 3-day period in November for over 30 years. Results: We estimate that over 30 million Bi-sensory Occupational Overload as a Result of Expressive Dysphasia (BOORED) exposures occur every day (15 million person hours) resulting in a daily loss of $252 million in productivity. The syndrome initially manifests as ptosis, lethargy, increasing somnolence, stertorous breathing and drooling. When severe and prolonged those affected may become comatose. It is exacerbated by the intensity of the expressive dysphasia, the number of sensory modalities affected, reduced modulation of auditory stimulus, reduced size combined with increased intensity of visual stimulation, reduced ambient light, increased ambient temperature, duration of exposure, repeated exposure and postprandial depression. of these, expressive dysphasia resulting in increasing loss of meaningful content combined with excessive hot air are the most important causative factors. Conclusion: Bi-sensory Overstimulation Resulting from Expressive Dysphasia syndrome is highly contagious. Large social gatherings that augment exposure to the syndrome are a significant occupational hazard especially for professionals working in the business, government, health and tertiary sectors. Strategies to reduce exposure are well documented and will be discussed using Haddon's 10 countermeasures.